2011
DOI: 10.1007/s00359-011-0670-5
|View full text |Cite
|
Sign up to set email alerts
|

Percent lipid is associated with body size but not task in the bumble bee Bombus impatiens

Abstract: In some group-living organisms, labor is divided among individuals. This allocation to particular tasks is frequently stable and predicted by individual physiology. Social insects are excellent model organisms in which to investigate the interplay between physiology and individual behavior, as division of labor is an important feature within colonies, and individual physiology varies among the highly related individuals of the colony. Previous studies have investigated what factors are important in determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 68 publications
(104 reference statements)
2
18
0
Order By: Relevance
“…Given this, we predicted that ovary size would correlate with lipid stores, either because bees with large ovaries avoided foraging, or because those with energy reserves could more readily enlarge their ovaries. However, we found no significant different differences between whole body lipid content and foraging classes (consistent with Couvillon et al, 2011 for B. impatiens ). This may be due to the controlled laboratory set-up, in which foragers did not engage in the normal, energetically costly foraging flights to collect resources.…”
Section: Discussionsupporting
confidence: 84%
“…Given this, we predicted that ovary size would correlate with lipid stores, either because bees with large ovaries avoided foraging, or because those with energy reserves could more readily enlarge their ovaries. However, we found no significant different differences between whole body lipid content and foraging classes (consistent with Couvillon et al, 2011 for B. impatiens ). This may be due to the controlled laboratory set-up, in which foragers did not engage in the normal, energetically costly foraging flights to collect resources.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have suggested several hypotheses for why larger workers may have lower survival (da Silva‐Matos & Garofalo, ). Some report larger workers having increased exposure to threats while foraging (Brian, ; Morse, ; O'Donnell et al, ) such as higher rates of parasitism (Gillespie, ; Malfi & Roulston, ; Muller et al, ; Schmid‐Hempel & Schmid‐Hempel, ), whereas others report lower tolerance to resource‐limited conditions (Couvillon & Dornhaus, ; Persson & Smith, ) potentially due to lower percentage lipid than smaller workers (Couvillon et al, ). Evaluating whether larger workers have lower survival due to foraging alone, rather than physiology, would be a critical next step in distinguishing these alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, return on investment, ROI, was calculated by dividing the lifetime resource collection of a worker of size i by its respective body mass, b , where E[ROI res,i ] = E[C res,i ]/b i (Table ). We also calculated ROI based on lipid content using the relationship between body size and lipids from Couvillon, Jandt, Bonds, Helm, and Dornhaus (). Because the lipid–body size relationship is concave, ROI based on lipids led to slightly higher optimum (see Supporting Information Appendix S3).…”
Section: Methodsmentioning
confidence: 99%
“…The average lipid content of EAB in our experiment (7.7%) also appears to be below the average of 14% for Coleoptera (Lease & Wolf, ). Breaking the integument (e.g., Couvillon et al., ) had no effect on the resulting fat extracted, nor did changing the position of the insects in the Soxhlet thimble. That these steps are not needed simplifies the process for this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed the effect of storage time on time to emergence and number of insects that emerged. Methods to evaporate water and procedures such as Soxhlet to solubilize and remove lipids (to obtain lean weight) have been reported in a number of insect studies (e.g., Bentz, ; Couvillon et al., ; Williams et al., ). However, we have found no methods for EAB.…”
Section: Introductionmentioning
confidence: 99%